Media Pembelajaran Audio Visual Berbasis Aplikasi Canva - Rahmatullah, Rahmatullah; Inanna, Inanna; Ampa, Andi Tenri (Jurnal Pendidikan Ekonomi Undiksha, 2020)
This study aims to develop audio visual learning media based on the Canva application. This study uses a Research and Development approach with the stages of initial analysis, material identification, product preparation, and testing. After the product is developed, a feasibility assessment is carried out by the expert to see the feasibility of the media design, match between content, design completeness, and attractiveness. Based on the results of expert judgment, the design of audio visual learning media based on the Canva application obtained a score of 82.28 percent with the very feasible category. The results of limited student responses obtained a score of 86.73 percent with the very feasible category. From the results of expert and student assessments, it means that the Audio-visual learning media based on the Canva application is suitable for use in pilot schools. The results of the first cycle 1 field trials were 67.13 percent and second cycleÂ  was 88 percent. The percentage of student learning outcomes shows an increase. This shows that it is easier for students to master labor material using audio-visual learning media based on the Canva application with very good criteria. Thus, the media developed can be used in online and offline learning.